Clinical significance of TP53 mutations in adult T‐cell leukemia/lymphoma. (17th August 2021) - Sakamoto, Yuma; Ishida, Takashi; Masaki, Ayako; Murase, Takayuki; Takeshita, Morishige; Muto, Reiji; Iwasaki, Hiromi; Ito, Asahi; Kusumoto, Shigeru; Nakano, Nobuaki; Tokunaga, Masahito; Yonekura, Kentaro; et al.
Summary: Adult T‐cell leukaemia/lymphoma (ATL) patients have a poor prognosis. Here, we investigated the impact of TP53 gene mutations on prognosis of ATL treated in different ways. Among 177 patients, we identified 47 single nucleotide variants or insertion‐deletions (SNVs/indels) of the TP53 gene in 37 individuals. TP53 copy number variations (CNVs) were observed in 38 patients. Altogether, 67 of 177 patients harboured TP53 SNVs/indels or TP53 CNVs, and were categorized as having TP53 mutations. In the entire cohort, median survival of patients with and without TP53 mutations was 1·0 and 6·7 years respectively ( P < 0·001). After allogeneic haematopoietic stem cell transplantation (HSCT), median survival of patients with ( n = 16) and without ( n = 29) TP53 mutations was 0·4 years and not reached respectively ( P = 0·001). For patients receiving mogamulizumab without allogeneic HSCT, the median survival from the first dose of antibody in patients with TP53 mutations ( n = 27) was only 0·9 years, but 5·1 years in those without ( n = 42; P < 0·001). Thus, TP53 mutations are associated with unfavourable prognosis of ATL, regardless of treatment strategy. The establishment of alternative modalities to overcome the adverse impact of TP53 mutations in patients with ATL is required.